Studies on the antioxidant activity of apigenin, luteolin and nevadensin using DFT - Huy, Nguyen Trung; Trang, Nguyen Van; Xuyen, Nguyen Thi; Hong, Cao Thi; Anh, Vo Thi Kieu; Thai, Vu Quoc; Cuong, Bui Van; Van, Tran Thi Thanh; Trang, Nguyen Van; Lam, Tran Dai; Hoan, Nguyen Thi; Thuy, Phan Thi; et al. (Vietnam Journal of Science and Technology, 2021)
The molecular properties of apigenin, luteolin and nevadensin which are three naturally flavonoid compounds have been studied theoretically by DFT method at 6-311++G(d,p) level. Both FMO analysis, mechanism, and kinetics studied suggested that compound Luteolin (compound 3) was a promising antioxidant agent. The results indicated that  HAT is thermodynamically preferred in the gas phase, and SPLET is the thermodynamically favorable pathway in methanol and water